PENGARUH PEMASARAN DIGITAL DAN HARGA TERHADAP KEPUASAN PELANGGAN PT. LEAPFROG INDONESIA - Arry Dwi Syahputra; Agustina Hutagalung (Jurnal Ekonomi dan Industri, 2024)
The analyze the influence of digital marketing and price on customer satisfaction at PT. Leapfrog Indonesia. This research is included in the category of causal associative research using a quantitative approach. The population in this research is all customers who buy products PT. Leapfrog Indonesia, the sampling technique uses incidental sampling technique. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the digital marketing and price have a positive and significant on customer satisfaction at PT. Leapfrog Indonesia.